2016
DOI: 10.1186/s12866-016-0866-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis 5′-nucleotidases with various functions and substrate specificities

Abstract: BackgroundIn Escherichia coli, nagD, yrfG, yjjG, yieH, yigL, surE, and yfbR encode 5′-nucleotidases that hydrolyze the phosphate group of 5′-nucleotides. In Bacillus subtilis, genes encoding 5′-nucleotidase have remained to be identified.ResultsWe found that B. subtilis ycsE, araL, yutF, ysaA, and yqeG show suggestive similarities to nagD. Here, we expressed them in E. coli to purify the respective His6-tagged proteins. YcsE exhibited significant 5′-nucleotidase activity with a broader specificity, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…As described above, in B. subtilis MC011, which lacked both functional pbuE and myo-inositol catabolism, the artificially introduced M. tuberculosis ino1 was "restored" to produce an active enzyme. This could enable the conversion of glucose into myo-inositol, since its substrate G6P is naturally supplied from glucose and also because its product MI1P is dephosphorylated by the intrinsic and constitutive YktC to form myo-inositol 22 . Accordingly, in order to enable the production of scyllo-inositol from glucose, we next introduced a previously established artificial pathway to convert myo-inositol into scyllo-inositol involving two inositol dehydrogenases, IolG and IolW 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, in B. subtilis MC011, which lacked both functional pbuE and myo-inositol catabolism, the artificially introduced M. tuberculosis ino1 was "restored" to produce an active enzyme. This could enable the conversion of glucose into myo-inositol, since its substrate G6P is naturally supplied from glucose and also because its product MI1P is dephosphorylated by the intrinsic and constitutive YktC to form myo-inositol 22 . Accordingly, in order to enable the production of scyllo-inositol from glucose, we next introduced a previously established artificial pathway to convert myo-inositol into scyllo-inositol involving two inositol dehydrogenases, IolG and IolW 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The key enzyme MI1PS is also found in some archaea and bacteria, including Mycobacterium tuberculosis, which, like B. subtilis, is a Gram-positive bacteria and possesses the myo-inositol biosynthesis pathway involving a functional ino1 21 . Within the genome of B. subtilis, there is no gene likely to encode MI1PS, but there is an intrinsic yktC gene encoding functional inositol monophosphatase 22 . Therefore, we speculated that simply expressing M. tuberculosis ino1 in B. subtilis may enable myo-inositol biosynthesis, and this myo-inositol can be introduced to a previously established cell factory platform that converts myo-inositol into scyllo-inositol 14 , enabling the production of scyllo-inositol from glucose in a single bacterial cell factory (Fig.…”
mentioning
confidence: 99%
“…Despite the important role of 5′-nucleotidases in cellular metabolism, only a few of these enzymes have been characterized in the gram-positive bacteria B. subtilis and B. amyloliquefaciens, the workhorses among industrial microorganisms. To identify genes encoding 5′-nucleotidases in Bacillus species, a search for genes homologous to earlier characterized 5′-nucleotidase genes in other bacteria, for example, E. coli, is often used as a suitable tool (Terakawa et al 2016;Zakataeva et al 2016). In this study, another method exploiting 5′-nucleotidase activity in gene products was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the essential role of soluble 5′-nucleotidases in bacterial metabolism and the design of industrially important strains, little information about the functions of these enzymes from Bacillus species could be found in the literature. Terakawa and coauthors reported the 5′-nucleotidase activities of several B. subtilis proteins (YqeG, YcaA, YutF, YcsE, and YktC) (Terakawa et al 2016) homologous to earlier described E. coli multifunctional enzymes that exhibit 5′-nucleotidase activity with respect to a remarkably broad and overlapping substrate spectrum (Matsuhisa et al 1995;Kuznetsova et al 2006). A HADSF member from B. subtilis, the 5′-nucleotidase YutF, was found to hydrolyze various purine and pyrimidine 5′-nucleotides, showing a preference for 5′-nucleoside monophosphates and, specifically, 5'-XMP (Zakataeva et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Industrial production of these nucleotides has traditionally relied in Gram-positive microorganisms and, among them, B. subtilis and other Bacillus species have a prominent role due to a large accumulation of inosine in the culture medium (Chen et al, 2005). Building on this natural occurrence, multiple studies have been performed to improve nucleotide accumulation, using strategies such as classical random mutagenesis (Matsui et al, 1982), culture optimization (Chen et al, 2005), target mutagenesis to avoid IMP degradation (Asahara and Mori, 2010) or introduction of nucleotidases that remove the phosphate group from IMP and GMP (Terakawa et al, 2016). A number of vitamins are also being produced industrially in B. subtilis as the chassis, mainly riboflavin, cobalamin and biotin.…”
Section: Bacillus Subtilismentioning
confidence: 99%